SYAIBANI ECONOMIC THOUGHT ON AL-KASB - Amiruddin, Muhammad Majdy (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The purpose of this research is to investigate the economic thought of al Imam Muhammad bin Hasan Al Syaibani focusing on Al-Kasb. Methodology used in this research is qualitative. The data collected from various litetaures on related productions specially in book Al Kasb. This research found that Al-Syaibani al-Kasb (production), that is, as seeking the acquisition of property through various halal methods. In economics, this activity is included in the production activity. The concept of maslahat is an objective concept of producer behavior because it is determined by the goal (maqashid) of shari'ah which is to maintain the benefit of humans in the world and the hereafter. Asy-Syaibani asserted that production is mandatory.